THE CAPITALIST DOMINANCE IN CHARLES DICKENS’ OLIVER TWIST - Yermia Immanuel Hendry Yanuarda; Eko Budi Setiawan (Humaniora Scientia, 2019)
The objectives of this study entitled The Capitalist Dominance in Charles Dickens’ Oliver Twist are (1) to find out the capitalist dominance described through the character of Mr.Bumble in Charles Dickens’ Oliver Twist. (2) to find out the impact of Mr. Bumble’s capitalism toward character Oliver in Charles Dickens’ Oliver Twist. The writer used library research to analyze the analysis. The main data is taken from novel of Oliver Twist. Some theories used to analyze the data are Character, Marxism, Capitalism, and Setting. Moreover, the approaches used in this research are sociological approach, psychological approach, marxism approach, ideological approach, and historical approach. For the result, the writer finds the capitalist dominance of Mr. Bumble. He follows the Oligarchic Capitalism and he controls and exploits Oliver without enough food and salary. He also becomes opportunist, snobby, and a wicked man. Moreover, from the impact of Mr. Bumble’s capitalism, Oliver becomes abandoned in the capitalist society, and becomes a social anxiety disorder child. Keywords : capitalist, capitalism, oligarchic capitalism